Identification and quantification of Acanthamoeba spp. within seawater at four coastal lagoons on the east coast of Australia - Binod Rayamajhee; Nathan L.R. Williams; Nachshon Siboni; Kiri Rodgers; Mark Willcox; Fiona L. Henriquez; Justin R. Seymour; Jaimie Potts; Colin Johnson; Peter Scanes; Nicole Carnt (Science of The Total Environment, 2023)

An Experimental Platform to Study Wind, Hydrodynamic, and Biochemical Conditions in the Littoral Zone During Extreme Coastal Storms - Brian Phillips; Forrest Masters; Britt Raubenheimer; Maitane Olabarrieta; Elise Morrison; Pedro Fernández-Cabán; Christopher Ferraro; Justin Davis; Taylor Rawlinson; Michael Rodgers (Oceanography, 2023)
Tropical cyclones and other extreme coastal storms cause widespread interruption and damage to meteorological and hydrological measurement stations exactly when researchers need them most. There is a longstanding need to collect collocated and synchronized measurements in areas where storms severely damage civil/coastal infrastructure. To fill this observational gap, researchers led by author Masters developed a state-of-the-art monitoring station called a “Sentinel.” Sentinels are intended for temporary installation on the beach between the mean tidal datum and the sand dunes and are engineered to operate in and measure extreme wind, storm surge, wave, and hazardous water quality conditions. They are envisioned as a shared-use resource—a hardened IoT (Internet of Things) platform set up in the right place at the right time to study wind and wave loads, coastal erosion and morphology changes, water quality, and other processes during extreme coastal storms.

The relative contributions of behavioral, biological, and psychological risk factors in the association between psychosocial stress and all-cause mortality among middle- and older-aged adults in the USA - Justin Rodgers; Adolfo G. Cuevas; David R. Williams; Ichiro Kawachi; S.V. Subramanian (GeroScience, 2021)

Morbidity compression or expansion? A temporal analysis of the age at onset of non-communicable diseases in India - Sanjay K. Mohanty; Justin Rodgers; Rajeev R. Singh; Radhe Shyam Mishra; Rockli Kim; Junaid Khan; Priyamadhaba Behera; S. V. Subramanian (GeroScience, 2021)